Good jobs, bad jobs and redistribution - Kjell Erik Lommerud; Bjørn Sandvik; Odd Rune Straume (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
We analyse the question of optimal taxation in a dual economy, when the government is concerned about the distribution of labour income. Income inequality is caused by the presence of sunk capital investments, which creates a .good jobs. sector due to the capture of quasi-rents by trade unions. We find that whether the government should subsidise or tax investments is crucially dependent on union bargaining strength. If unions are weak, the optimal tax policy implies a combination of investment taxes and progressive income taxation. On the other hand, if unions are strong, we find that the best option for the government is to use investment subsidies in combination with either progressive or proportional taxation, the latter being the optimal policy if the government is not too concerned about inequality and if the cost of income taxation is sufficiently high. – – In dem Beitrag wird die Frage der optimalen Besteuerung in einer Wirtschaft mit zwei Sektoren untersucht, in der die Regierung an der Verteilung des Arbeitseinkommens interessiert ist. Einkommensungleichheit wird dann durch versunkene Kapitalinvestitionen verursacht, die einen Sektor mit .guten. Arbeitsplätzen schaffen, der durch die Aneignung von Quasi-Renten durch Gewerkschaften entsteht. Ob die Regierung Investitionen subventionieren oder besteuern soll, hängt entscheidend von der Verhandlungsst ärke der Gewerkschaften ab. Wenn die Gewerkschaften schwach sind, dann sieht die optimale Steuerpolitik eine Kombination aus Investitionssteuern und progressiver Einkommensbesteuerung vor. Im Falle von starken Gewerkschaften zeigt sich, daß die beste Handlungsalternative für die Regierung aus dem Einsatz von Subventionen in Kombination mit entweder progressiver oder proportionaler Besteuerung besteht, wobei die letztere dann optimal ist, wenn die Regierung nicht zu sehr an Ungleichheit interessiert ist und wenn die Kosten der Einkommensbesteuerung hinreichend hoch sind.
Keywords: H2; J42; J51; 330; Rent sharing; segmented labour markets; optimal taxation; redistribution